1979
DOI: 10.1007/bf01869166
|View full text |Cite
|
Sign up to set email alerts
|

Voltage fluctuations at the frog sartorius motor endplate produced by a covalently attached activator

Abstract: The depolarization that develops after covalent attachment of trimethylammonium benzoyl to the dithiothreitol-reduced frog sartorius acetylcholine receptor is accompanied by a small increase in voltage fluctuations. The amplitude of the elementary voltage event produced by the covalently attached activator is about 0.04 microV, almost an order of magnitude below the acetylcholine shot-effect amplitude in the control preparation, and about one-fourth the acetylcholine shot amplitude after disulfide-bond reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Once attached, QBr activated the channel in its trans -form, that is at 500 nm or in the dark, but could be switched to an inactive cis -form by irradiation with 330 nm light. The resulting light-activated nAChR could be used to stimulate reversibly Electrophorus electroplaques, frog muscles and rat myoballs with light 28,29,31,32 . At the time these studies were carried out, however, receptors could not be manipulated genetically and expressed heterologously, so the impact of synthetic photo-switches on neuroscience research remained limited.…”
Section: Discussionmentioning
confidence: 99%
“…Once attached, QBr activated the channel in its trans -form, that is at 500 nm or in the dark, but could be switched to an inactive cis -form by irradiation with 330 nm light. The resulting light-activated nAChR could be used to stimulate reversibly Electrophorus electroplaques, frog muscles and rat myoballs with light 28,29,31,32 . At the time these studies were carried out, however, receptors could not be manipulated genetically and expressed heterologously, so the impact of synthetic photo-switches on neuroscience research remained limited.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Because the unreacted molecules are washed out of the preparation after the tethering reaction, there is no chance that they can also function as competitive antagonists or "open-channel blockers." Their disadvantage is that, like all known agonists, they eventually desensitize receptors, so that the number of open channels decreases with time (31,32). This shortcoming is avoided by the photoisomerizable tethered agonist, QBr (13, 65; Figure 1).…”
Section: (86)mentioning
confidence: 99%
“…We have therefore combined whole-cell and single-channel measurements on cultured rat myoballs in order to extend earlier experiments with tethered agonists at the ACh receptor of frog muscle (Cox et al 1979) and ofElectrophorus electroplaques (Lester et al 1980). As found previously, the ACh channel can be activated by a single tethered agonist, although other channel properties, such as the conductance, kinetics, and voltage dependence, are very similar to those seen with reversibly bound agonists.…”
Section: Introductionmentioning
confidence: 96%
“…They eliminate the first step in the agonist-receptor interaction, the diffusion-limited formation of an initial complex (Burgen, 1966). The tethered agonist is present at a very high effective local concentration: Cox, Kawai, Karlin & Brandt (1979) estimated -1 M. If a reversibly TETHERED NICOTINIC AGONISTS AT RAT MYOBALLS bound agonist molecule were studied at such concentrations, channel block by the agonist itself would intolerably complicate the current records. In addition, by comparing the fractional conductance with the fraction of active (trans) tethered QBr, it has been shown that the open state of the receptor is controlled by the configuration of a single tethered QBr molecule (Lester et al 1980).…”
Section: Introductionmentioning
confidence: 99%